Declining prevalence of STI in the London sex industry, 1985 to 2002. Issue 5 (30th September 2004) - Ward, H; Day, S; Green, A; Cooper, K; Weber, J
Abstract : Objectives: To describe major changes in the London sex industry between 1985 and 2002 and assess the implications for sexually transmitted infection (STI) risk. Method: A descriptive study comparing women who first attended a sex work clinic between 1996 and 2002 and those first attending from 1985 to 1992; a nested case-control study. 1050 female sex workers took part. The setting was a specialist clinical service for sex workers based in a London genitourinary medicine (GUM) clinic, and fieldwork in west London. The main outcome measures were reported condom use and prevalent STI. Results: Over the period of the study there was a significant increase in the proportion of sex workers not born in the United Kingdom (from 25% to 63%, p<0.001), and women entered sex work at an older age (median 24 years compared with 20 years, p<0.001). Condom use increased (with the exception of oral sex). There was a significant decline in the proportion of participants reporting a previous STI (32% compared with 80%, p<0.001) and the prevalence of acute STI declined from 25% to 8% (p<0.001). Acute STI was associated with younger age, younger age at first sex work, being new to sex work, and inconsistent condom use. In a multivariate analysis unprotected sex with clients was the only significant risk. Conclusion: Major restructuring of the sex industry, including the shift to a primarily migrant workforce, has been associated with a steep decline in acute STI, undermining popular assumptions that migrant sex workers are central to the ongoing STI epidemic. We attribute the decline in acute STI to an increase in safer sex.